Charge-based MOSFET model based on the Hermite interpolation polynomial. (April 2017) - Colalongo, Luigi; Richelli, Anna; Kovacs, Zsolt
Highlights: Charge-based compact MOSFET model based on the Hermite interpolation polynomial. It retains the same simplicity of the most advanced charge-based compact MOSFET models. It is extremely accurate: the non-linearity in the channel are accounted for. The slope factor is rigorously defined in all regions of operation. It represents a promising platform for the next generation of charge-based compact models. Abstract: An accurate charge-based compact MOSFET model is developed using the third order Hermite interpolation polynomial to approximate the relation between surface potential and inversion charge in the channel. This new formulation of the drain current retains the same simplicity of the most advanced charge-based compact MOSFET models such as BSIM, ACM and EKV, but it is developed without requiring the crude linearization of the inversion charge. Hence, the asymmetry and the non-linearity in the channel are accurately accounted for. Nevertheless, the expression of the drain current can be worked out to be analytically equivalent to BSIM, ACM and EKV. Furthermore, thanks to this new mathematical approach the slope factor is rigorously defined in all regions of operation and no empirical assumption is required.